Application of social media analytics in tourism crisis communication. Issue 15 (14th September 2019) - Park, Deukhee; Kim, Woo Gon; Choi, Soojin
ABSTRACT: Given the newly established communication environment of social media and highly unpredictable crisis situations, this study questioned how tourists facing an unexpected crisis situation use social media to communicate and search for information. To this end, this study developed a multi-phased social media analytic framework (data crawling, data processing and text mining, social network analysis, semantic network analysis, and network visualization) to assess the structure of information exchanges between the members of a tourism organization's social network community and identified influential actors and information content within the social network. This study's findings suggest genuine ways of relating with and utilizing opinion leaders and influencers in social media marketing communication as well as crisis communication. The authors expect this proposed methodological framework of social media analytics to help other scholars scientifically identify and implement the proper methodologies for utilizing social media data.